Systemic inflammatory response in predicting outcomes of patients undergoing curative resection for oral squamous cell carcinoma. Issue 5 (June 2022) - Zubair, Farhan; McMahon, Jeremy; Kryklyas, Ganna; Wicks, Catherine
Abstract: This study aimed to evaluate the prognostic significance of the modified Glasgow prognostic score (mGPS), neutrophil:lymphocyte ratio (NLR), and platelet:lymphocyte ratio (PLR) in patients undergoing resection of oral squamous cell carcinoma (OSCC) with curative intent. We also aimed to explore the relation between activated systemic inflammation and adverse tumour characteristics. Between February 2006 and December 2019, data on 825 patients undergoing curative resection of OSCC were retrospectively gathered. Preoperative C-reactive protein and serum albumin levels were obtained to calculate a mGPS. Full blood count parameters were collected to calculate NLR and PLR values. Categorical factors were analysed using the chi squared test. Multivariate regression was performed to identify independent prognostic variables and the predictive value of each model generated. For disease-specific survival (DSS) and overall survival (OS), mGPS (DSS and OS both p<0.001), NLR (DSS and OS both p<0.001) and PLR (DSS and OS both p<0.001) were significant on univariate analysis. Independent predictive variables for DSS included mGPS, clinical node stage, categorised depth of tumour invasion, non-cohesive invasive front, and lymphovascular invasion. The concordance index was acceptable (0.756) for this model. Replacing mGPS with NLR or PLR as a marker of systemic inflammation demonstrated the same preoperative variables as independently predictive for DSS. The concordance index for these models were acceptable (NLR 0.76 and PLR 0.756). The systemic inflammatory response is prognostically significant in patients undergoing curative resection of OSCC. The potential link between an inflammatory tumour microenvironment and activated systemic inflammation merits further investigation.